The current landscape of the antimicrobial peptide melittin and its therapeutic potential - Zhang, Hai-Qian; Sun, Chengbiao; Xu, Na; Liu, Wensen (Frontiers in Immunology, 2024)
Melittin, a main component of bee venom, is a cationic amphiphilic peptide with a linear αhelix structure. It has been reported that melittin can exert pharmacological effects, such as antitumor, antiviral and anti-inflammatory effects in vitro and in vivo. In particular, melittin may be beneficial for the treatment of diseases for which no specific clinical therapeutic agents exist. Melittin can effectively enhance the therapeutic properties of some first-line drugs. Elucidating the mechanism underlying melittin-mediated biological function can provide valuable insights for the application of melittin in disease intervention. However, in melittin, the positively charged amino acids enables it to directly punching holes in cell membranes. The hemolysis in red cells and the cytotoxicity triggered by melittin limit its applications. Melittin-based nanomodification, immuno-conjugation, structural regulation and gene technology strategies have been demonstrated to enhance the specificity, reduce the cytotoxicity and limit the off-target cytolysis of melittin, which suggests the potential of melittin to be used clinically. This article summarizes research progress on antiviral, antitumor and anti-inflammatory properties of melittin, and discusses the strategies of melittin-modification for its future potential clinical applications in preventing drug resistance, enhancing the selectivity to target cells and alleviating cytotoxic effects to normal cells.